Caracalla and the Immortal Gods - Galimberti, Alessandro (ARYS. Antigüedad: Religiones y Sociedades, 2025)
The Constitutio Antoniniana, the Temple to the Severans at Lepcis Magna, the cult of the god Luno at Carrhae and the Temple of Faustina on the slopes of Taurus are four significant moments of Caracalla’s religious policy and highlight the interreligious character of his choices.
Keywords: Caracalla; Carrhae; Constitutio Antoniana; Lepcis Magna; Religious Policy; Taurus